(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2023)
Speech by Venezuelan poet Rafael Cadenas, upon receiving the Premio Cervantes 2022. Ceremony held on April 24, 2023 in Alcalá de Henares.